EXPECTATIONS OF UNDERGRADUATE MATHEMATICS STUDENTS REGARDING FINANCIAL EDUCATION (Interdisciplinary Studies Journal, 2024)
This research sought to understand aspects related to financial education from the perceptions of students of the Mathematics Degree Course at IFMA, Campus Buriticupu, from the perspective of Critical Mathematics Education by Skovsmose and mathematics teacher training by D'Ambrosio. Six academics enrolled in the discipline of financial mathematics participated in the research. A qualitative approach was adopted and for data collection a questionnaire with 12 open questions was used. For data analysis, content analysis was supported, which allowed the categorization of their statements regarding: characterization of the participant; motivations and expectations of academics in relation to financial education; knowledge and skills in financial education and perceptions of the challenges and opportunities that could arise from financial education. It was observed that they had no contact with the subject in basic education and until the present moment (fourth semester of the Mathematics course) and when they comment on the importance of financial education, they only relate it to the value of money. It was concluded that the insertion of this object of knowledge in the students' path can help them both in the development of knowledge related to financial and social issues. In addition to helping them to be critical, reflective and autonomous.
Keywords: Teacher Education; Critical Mathematics Education; Financial math; Degree in Mathematics